Adaptive consensus for heterogeneous multi-agent systems under sensor and actuator attacks. (December 2020) - Meng, Min; Xiao, Gaoxi; Li, Beibei
Abstract: This study investigates the leader-following consensus problem for heterogeneous multi-agent systems subject to both sensor and actuator attacks. The attacks considered in this paper are false data injection attacks. A novel adaptive controller is proposed to guarantee that the consensus tracking is achieved with cooperative uniform ultimate boundedness for the multi-agent systems in the simultaneous presence of sensor and actuator attacks. As the whole state information is unknown, the adaptive dynamics are designed on the basis of the received compromised/uncompromised output information. Simulations are carried out to demonstrate the effectiveness of the obtained results.